Pautas para el reconocimiento de créditos comerciales en el procedimiento concursal peruano - Enrique Palma Navea, Jose Enrique (2024)
The article analyzes from the perspective of bankruptcy law, the credits generated by relations of a commercial nature between a debtor subject to bankruptcy and its creditors. It also develops the evidentiary requirements necessary to prove before the Peruvian insolvency authority the origin, existence, legitimacy, titularity and quantity of this type of credit, in order that the holder of such credits may obtain the recognition of its credits before the bankruptcy authority, within the framework of the bankruptcy procedure. The analysis is made on the basis of diverse Indecopi jurisprudence.